2012
DOI: 10.1088/0957-4484/23/46/465603
|View full text |Cite
|
Sign up to set email alerts
|

Programmable self-assembly of carbon nanotubes assisted by reversible denaturation of a protein

Abstract: Self-assembly of pristine multi-walled carbon nanotubes (CNTs) in aqueous dispersion using a protein, bovine serum albumin (BSA), has been demonstrated. Step-wise conformational changes in BSA as a function of temperature have been deployed to direct the assembly of nanotubes. More specifically, CNTs distributed randomly in native BSA at 35 °C as well as completely denatured BSA solution at 80 °C self-assemble in the intermediate temperature range of 45-65 °C, as evident from scanning and transmission electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Our study of aggregation also opens the door to various potential applications. Compared to previous BSA–SWCNT studies, our EM showed much higher protein density per SWCNT . Combined with aggregate preferences for protein types, there is potential to utilize aggregation for the detection , and extraction of low-concentration species.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our study of aggregation also opens the door to various potential applications. Compared to previous BSA–SWCNT studies, our EM showed much higher protein density per SWCNT . Combined with aggregate preferences for protein types, there is potential to utilize aggregation for the detection , and extraction of low-concentration species.…”
Section: Discussionmentioning
confidence: 57%
“…Compared to previous BSA–SWCNT studies, our EM showed much higher protein density per SWCNT. 53 Combined with aggregate preferences for protein types, there is potential to utilize aggregation for the detection 54 , 55 and extraction of low-concentration species. Lastly, the new understanding of temperature-dependent DNA–SWCNT associations can lead to novel methods of bioresponsive self-assembly.…”
Section: Discussionmentioning
confidence: 99%
“…BSA at pH 6.5 (all the experiments in this work had a suspension pH in the range of 6-7) contains only deprotonated hydroxyl groups (-COOH) on the surface, whereas -NH 2 groups are embedded within the globular structure of BSA. 32 Therefore, BSA can interact at the ends of the curcumin molecule at phenolic -OH and methoxyl groups resulting in a quick arrest of curcumin particle growth in all directions (schematic shown in Fig. 10).…”
Section: Proposed Mechanism For Formation Of Curcumin Superstructuresmentioning
confidence: 99%
“…Being hydrophobic in nature, CNTs are subjected to van der Waals interactions, which results in them being found in the form of selfassembled aggregates, which makes them quite insoluble in water. Nithiyasri et al [227] have investigated the possibility of self-assembling CNTs in aqueous dispersions using a water-soluble protein; bovine serum albumin (BSA). …”
Section: Properties Of Cntsmentioning
confidence: 99%
“…They concluded that CNTs selfassemble in the intermediate temperature range of 45-65°C in both native BSA at 35°C, as well as denatured BSA solution at 80°C[227].…”
mentioning
confidence: 99%